Otimização, validação e aplicação de método para determinação da concentração residual de difenoconazol em morangos após múltiplas aplicações - Heleno, Fernanda Fernandes; Queiroz, Maria Eliana Lopes Ribeiro de; Neves, Antônio Augusto; Oliveira, André Fernando de (Química Nova, 2013)
Difenoconazole residues in strawberry fruit cultivated in pots were estimated using the solid-liquid extraction with low temperature partition (SLE/LTP) method for sample preparation and gas chromatography with electron capture detection (GC/ECD) for analysis. The optimized method presented excellent recovery values from fortified samples and reproducibility (average recovery values ≥ 98%; CV values < 15%). Linearity of response was demonstrated (r = 0.995) with a detection limit of 9 µg kg-1. The method was successfully applied for the determination of difenoconazole residues in strawberries. Based on these results, the fungicide dissipates quickly, but the residual concentration increases after multiple applications.
Keywords: Pesticide analysis; Strawberry; Gas chromatography